Error analysis an investigation of the interlanguage of high school senior students - Guerrero, Bernard Joseph E. (College of Arts and Letters, University of the Philippines Diliman, 2008)
The study is an error analysis of the free essays, written by senior students of Mariano Marcos State University - Science High School, which investigates the types and nature of their errors, the frequency of error occurrence, percentage and ranking. It utilizes Larry Selinker's interlanguage theory as the framework of the study. The interlanguage refers to the interim grammars constructed by second language learners. It suggests a half-way position or stage between knowing and not knowing the target language on the part of the learners of a second language. The data were analyzed using a simplified version of Corder's algorithm for error analysis. The study reveals that a total of 244 morphosyntactic errors and 54 lexical errors have been committed by the subjects. The results of the study have been arranged from the most frequently occurring errors to the least occurring errors. The following specific errors have been found: subject-verb agreement errors, article errors, position errors, pronoun errors, conjunction errors, -be linking verb errors, verb tense errors, missing antecedent, do verb + stem verb error, quantifier number confusion error, misplaced modal, word order, word choice, ambiguous errors, and incomplete construction of sentences. Strategies such as overgeneralization, ignorance of rule restriction, incomplete application of rules, and false concepts hypothesized have also been established as the hypothesized causes of the errors found in the study.